Paintings and drawings of Fatima Meer in the context of the struggle narrative at Constitutional Hill - Mdluli, Same (My University, 2010)
ABSTRACT In mid-1976 following the Soweto riots a group of women that were part of the newly formed Federation of Black Women were detained under Section 6 of the Terrorism Act at the Women’s Jail in Johannesburg. Fatima Meer was one of these women and she created twenty paintings and drawings in secret during this time to show the realities of prison life during her incarceration. My report examines firstly how these paintings have been displayed at the Women’s jail in relation to the history of the site and then explores how these either add to or detract from the way visitors experience and understand the space of the prison. I argue that Meer’s paintings were not only a way of documenting the realities of prison life but rather an act of defiance that challenged a masculine and narrowly political representation of the history of the liberation struggle. The paintings provided the basis for us to explore a cultural, rather than a narrowly political, narrative that suggests other dimensions of opposition to apartheid, making for a richer, more diverse, narrative that is inclusive towards both women and men is conscious of curatorial practices that could make for a fuller visitor experience and participation